VIDEO LEARNING DEVELOPMENT IN SKILLS ENHANCEMENT TECHNIQUES TO MEET THE INSTALLATION OF INFUSION COMPETENCE CORE NURSING SKILLS - Aryani, Atik; ., Antia; Charolina, Astri (JURNAL PROFESI || MEDIA PUBLIKASI PENELITIAN, 2014)
Infuse therapy is an integral part of a nurseâs professional practice. Technique of infuse administration is included in learning of clinical nursing skill. There are several learning methods used in clinical learning, such as, a video of learning. One of advantages of video-assisted learning is the video can show real skill and activity, reduces cost expended in presentation and the use can be repeated. The purposes of the research are to make and develop an effective and efficient learning video in attempt of improving skill of infuse administration of nursing students, to obtain a picture about acceptance and satisfaction of nursing students on materials of the learning video, to know and to test if there is a difference between students who are using the learning video and those who are not, as media of learning.The approach used in developing of the learning media was a quantitative experimental method with factorial 2 x 2 design. After an analysis with two-ways ANOVA, F test was used to examine each factor. Results: There was an effect of using the learning video on skill of infuse administration among the students, there is a different technical skill of infuse administration between students who had used the learning video and those who had not as a media of learning. It could be seen from Fcalculation=5.044 and r value = 0.030<0.05. Conclusion: Students with video as a learning media in learning of infuse administration technique had better skill of infuse administration technique than those who had not used it. Â  Keywords: Learning video, infuse, nurse